Most children who are allergic to cow's milk tolerate yogurt. Issue 12 (December 2018) - Küçükosmanoğlu, Ercan; Özen, Evrim; Eltan, Sevgi Bilgiç; Özkars, Mehmet Yaşar; Keskin, Özlem
Objective: Cow's milk allergy is the most common food allergy in childhood. Changes occur in the protein structure of milk during yogurt fermentation. This study aimed to determine whether children who are diagnosed with a cow's milk allergy can tolerate yogurt. Methods: We performed a yogurt challenge test on 34 children who were diagnosed with a cow's milk allergy in our Pediatric Allergy Outpatient Clinic. The mean age of 24 male and 10 female children was 24 ± 13 months. Results: A reaction was observed in 17 (50%) patients, whereas no reaction was observed in the other 17 (50%) during an oral yogurt challenge test that was performed in all of the 34 patients with a cow's milk allergy. Cow's milk-specific immunoglobulin E levels were significantly lower in the group of children who could tolerate yogurt than in the group of children who could not tolerate yogurt. Conclusion: Yogurt is tolerated by half of children with a cow's milk allergy when subjected to a challenge test performed with yogurt, which is consumed as much as milk in Turkey.